INTEGRATED NUTRIENT SUPPLY AND MANAGEMENT FOR POTATO PRODUCTION IN MID HILLS OF SHIMLA - Sood, M C (Potato Journal, 2013)
Field experiments on integrated nutrient supply and management were conducted on sandy loam soil during 2003-2004 in mid hills of Shimla. The results revealed that combined use of organic and inorganic in the ratio of 1:3 significantly increased plant growth parameters, which was reflected in tuber yield and nutrients uptake. The higher tuber yield under integrated use of organic and inorganic was mainly due to higher proportion of large and medium size tubers.